Deep Learning Instructional Approach for Developing Students' Understanding of Fiʿil Muḍāriʿ in Arabic Morphology - Azizah, Siti Zahrotul; Ghufron, Zaki; Ubaidillah, Ubaidillah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aimed to examine the effect of the Deep Learning Approach on students’ understanding of qawāʿid in Arabic language learning, particularly in learning ṣharf with a focus on fiʿil muḍāriʿ. To achieve this objective, the study employed a quantitative approach using a quasi-experimental nonequivalent control group design. The study was conducted with eleventh-grade students at MAN 2 Kota Serang during the 2025/2026 academic year. Purposive sampling was employed, involving 36 students in the experimental group and 32 students in the control group. Data were collected using validated pretest and posttest instruments and analyzed using SPSS. Because the data were not normally distributed, the Mann–Whitney U test was employed. The results revealed no significant difference between the two groups on the pretest; however, a statistically significant difference was observed on the posttest. The experimental group achieved a higher mean posttest score (97.92) than the control group (90.78), indicating that the Deep Learning Approach effectively enhanced students’ understanding of qawāʿid.